IDENTIFIKASI NILAI KONSELING DALAM BUDAYA BAU NYALE DI PULAU LOMBOK - Husniati; Mohamat Hadori; Wawan Juandi (Konseling At-Tawazun, 2024)
Indonesia is a country that has a diversity of tribes and cultures spread across the islands, one of which is the Sasak tribe on the island of Lombok. The aim of this research is to identify the value of counseling in the bau nyale culture on the island of Lombok. This research uses qualitative research methods with an ethnographic type of research. The research results show that the counseling values contained in the bau nyale culture are being a person who is patient, sacrificial, willing to sacrifice, fair, wise and has a high social spirit.